Volume 2: Integrity and Corrosion; Offshore Issues; Pipeline Automation and Measurement; Rotating Equipment 2000
DOI: 10.1115/ipc2000-235
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Pipeline Collapse Resistance

Abstract: Much research has been performed over the past twenty-five years to refine our basic understanding of tubular stability, which includes bifurcation, imperfect systems, factors influencing tubular stability and post-buckling behaviour. Tubular instability resulting from load combinations is not a trivial topic, particularly when inelastic material behaviour occurs. Many influencing factors must be considered when attempting to understand (and predict) the onset of instability. Many existing colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…It has been shown for the first time that the cold forming of line pipes has a significant effect in determining the level of residual stresses in a line pipe, and should be taken into consideration for the prediction of 1 the ultimate external pressure and pressurized bending capacity. Similar conclusions have been reported in the experimental works [3], [4]. A finite element study has been reported on the effect of UOE cold bending process on the collapse pressure by Herynk et al [5] who employed an advanced two-surface plasticity model using a cyclic-plasticity model with nonlinear kinematic hardening.…”
Section: Introductionsupporting
confidence: 85%
“…It has been shown for the first time that the cold forming of line pipes has a significant effect in determining the level of residual stresses in a line pipe, and should be taken into consideration for the prediction of 1 the ultimate external pressure and pressurized bending capacity. Similar conclusions have been reported in the experimental works [3], [4]. A finite element study has been reported on the effect of UOE cold bending process on the collapse pressure by Herynk et al [5] who employed an advanced two-surface plasticity model using a cyclic-plasticity model with nonlinear kinematic hardening.…”
Section: Introductionsupporting
confidence: 85%
“…It has been shown for the first time that the cold forming of line pipes has a significant effect in determining the level of residual stresses in a line pipe, and should be taken into consideration for the prediction of ultimate external pressure and pressurized bending capacity. Similar conclusions have been reported in the experimental works [9], [10]. A finite element study has been reported on the effect of UOE cold bending process on the collapse pressure by Herynk et al [11], employing an advanced two-surface cyclic-plasticity model with nonlinear kinematic hardening.…”
Section: Literature Reviewsupporting
confidence: 86%
“…The dependency of collapse on the sequence of loading is related to the loading/unloading sequences (and resulting material stiffness changes) that arise around the circumference of the pipe cross section. The dependency of collapse on the load path is also discussed in [13] for B---~P and P--~B, as well as for tension plus pressure (T---~P).…”
Section: Fea For the P--~b Testmentioning
confidence: 99%